Glosa sobre a universidade, a formação e as disciplinas do saber, por ocasião de um concurso universitário - Waizbort, Leopoldo (ARS, 2011)
What is the sense in talking about education today? And how to build the form of an academic memorial? These are the axes that guide an argumentation of official examination, wich this text reproduces.